Biopolítica e neoliberalismo: a vigilância sanitária no limite da utilidade para o comércio internacional - Campos Motta, Renata (Revista de Direito Sanitário, 2008)
Taking into consideration the relationships between health and international trade throughout the 90's, this paper analyzes the ways in which the Brazilian State Reform, in the health surveillance sector, specifically, the creation of the National Health Surveillance Agency (Anvisa) is related to the advance of the multilateral trade regime. Considering Foucault´s reflexions on neoliberalism, this work analyses how the neoliberal questions of "how" and "until what limit it is useful" the state intervention in the economy have informed both international and domestic markets demands about the characteristics of adopted the institutional design.